ISU DAN TREN PENELITIAN PENGEMBANGAN BAHAN AJAR BAHASA ARAB TAHUN 2017-2020 - Nurul Aini Baarid; Kamal Yusuf (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Abstract The aim of this study is to determine the research tren for the development of Arabic teaching materials in year 2017-2020 of Postgraduate students at UIN Sunan Ampel in Surabaya whether this tren is consistent with the development of Industrial Revolution 4.0, which is linked by a system that unites the real and virtual world, or vice versa. The research method used is descriptive analysis research by collecting library data, recording and processing literacy data related to these issues. The results showed that research on the development of Arabic teaching materials to improve four language skills was ranked first as the most emerging research topic with a percentage of 0.6%, secondly research on the design of Arabic teaching materials with a percentage of 0.08%, third research on the Arabic learning curriculum for comparative studies and its development with a percentage of 0.08%, then research on the pedagogical and professional competences of teachers and their effects on student achievement with a percentage of 0.07%, then technology-based research for learning Arabic with a value 0.07%, research on the influence of the language environment by 0.04%, then research on the development of an assessment instrument of 0.02% and research on strategies, media, and methods of learning Arabic as well as book analysis research respectively ranked last with a percentage of 0.01% as the least frequent research topic. Keywords: Development research, Teaching materials, Arabic language